PENGGUNAAN MODEL NUMBERED HEADS TOGETHER (NHT) DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS IV SEKOLAH DASAR - Istiqomah, Nurul (KALAM CENDEKIA PGSD KEBUMEN, 2013)
Abstract: The Using Model Numbered Heads Together (NHT) in Improving IPS Learning Grade IV Elementary School. This research uses class actions research methods are carried out in the three cycles. Each cycle consists of planning, action, observation, and reflection. The data sources of this research is the fourth grade students of Sidomukti elementary school in academic year 2011/2012 which amaunted to 18 students, consist of 10 men and 8 women. Data collecting methods are collected through observation, interview, test and documentation. The validity of data using the triangulation instrument. The data Analysis is used by this research is kuantitatif and kualitatif data analysis. The result showed that the using Model Numbered Heads Together (NHT) can improve learning about technological developing Elementary School fourth grade students Wadas year 2013. Keywords: Model Numbered Heads Together (NHT), Improved Learning, IPS Abstrak: Penggunaan Model Numbered Heads Together (NHT) dalam Peningkatan Pembelajaran IPS Siswa Kelas IV Sekolah Dasar. Penelitian ini bertujuan untuk mendeskripsikan langkah langkah penggunaan model Numbered Heads Together (NHT) dalam peningkatan pembelajaran IPS tentang perkembangan teknologi siswa kelas IV SDN Wadas Tahun 2013. Penelitian ini menggunakan metode penelitian tindakan kelas yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV SD Negeri Wadas tahun 2013 yang berjumlah 33 siswa, terdiri dari 15 laki laki dan 18 perempuan. Teknik pengumpulan data adalah dengan observasi, wawancara, tes dan dokumentasi. Validasi data menggunakan teknik triangulasi data. Analisis data yang digunakan dalam penelitian ini adalah analisis data kualitatif dan kuantitatif. Hasilnya menunjukkan bahwa penggunaan model Numbered Heads Together (NHT) dapat meningkatkan pembelajaran IPS tentang perkembangan teknologi siswa kelas IV SD Negeri Wadas Tahun 2013. Kata Kunci: Model Numbered Heads Together (NHT), Peningkatan Pembelajaran, IPS